COMPUTATIONAL DYNAMIC ANALYSIS OF SINGLE-MASS FREELY SHAKING CONVEYERS WITH CENTRIFUGAL VIBRATION EXCITER - Alisverisci, Fuesun (SPRINGER, 2008)
Single-mass freely shaking (vibrational) conveyers with a centrifugal vibration exciter transmit their load based oil the jumping method. The trough is oscillated by a common unbalanced-mass driver. This vibration causes the load to move forward and upward. The moving loads jump periodically and move forward with relatively small vibration. The movement is strictly related to the vibrational parameters. Tills is applicable ill laboratory conditions in the industry that accommodate a few grams of loads, LIP to those that accommodate tons of loading capacity. Ill this study, the variation of motional parameters has been represented graphically using the software Mathemalica with respect to i) vibrational parameters, ii) parameter of the unbalanced mass, iii) operation mode, iv) friction coefficient, and v) angle of attack. The proper parameters for the transport of the numerous loads and the transportation velocity call be chosen with the help of the graphics. The results obtained in this study have been compared with the experimental results in the pertaining literature, and have been found to be well matched.
Keywords: shaking (vibrational) conveyers; operation mode; unbalanced mass; Engineering; Mathematics; Physics